Asymmetrical Bimodal Distributions with Screw Modes - Gordevskyy, V.D.; Sazonova, E.S. (Журнал математической физики, анализа, геометрии, 2011)
The Boltzmann equation for the model of hard spheres is considered. Approximate bimodal solutions for the Boltzmann equation are built for the case when the Maxwellian modes are screws with di®erent degrees of infinitesimality of angular velocities. Some su±cient conditions for the minimization of the uniform-integral remainder between the sides of the Boltzmann equation are obtained.